Тепловые и гидромеханические характеристики пластин с меняющимся по длине пластины сечением канала - Арсеньева, Ольга Петровна; Товажнянский, Леонид Леонидович; Перевертайленко, Александр Юрьевич; Долгоносова, Е. А. (НТУ "ХПИ", 2010)
The experimental data of the heat and hydromechanical characteristics for plates with variable channels profile along plate length is presented. Plate consists of four zones. The equations for hydraulic resistance factor and Nusselt number every zone are obtained. These dates are basic for methods of design vacuum condensers with variable of channels square.
Keywords: теплообменники; пластинчатые теплообменники; сечение канала; конденсация пара; теплоотдача; гидравлическое сопротивление; конденсаторы